1995
DOI: 10.1093/carcin/16.7.1659
|View full text |Cite
|
Sign up to set email alerts
|

DNA damage in UVB-irradiated keratinocytes

Abstract: A DNA lesion which results from the breakdown of a pyrimidine base leaving a formamido remnant has been associated with oxidative stress. This lesion is shown to be produced in keratinocytes irradiated in culture with UVB light. The amount of formamido lesion produced is comparable to the amount of the 8-hydroxyguanine lesion. The two lesions were measured by 32P-postlabeling and electrochemical detection methods respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 0 publications
0
9
0
1
Order By: Relevance
“…(42)(43)(44) However, those techniques had a limitation derived from the artifactual oxidation of DNA during its extraction. It was recently reported that relatively low doses of UVB (62.5-500 mJ/cm 2 ) cause dose-dependent increases in 8-OH-dG, and DNA from unirradiated normal human epidermal keratinocytes contains 1.49 ± 0.11 8-OH-dG residues per 10 6 dG.…”
Section: Discussionmentioning
confidence: 99%
“…(42)(43)(44) However, those techniques had a limitation derived from the artifactual oxidation of DNA during its extraction. It was recently reported that relatively low doses of UVB (62.5-500 mJ/cm 2 ) cause dose-dependent increases in 8-OH-dG, and DNA from unirradiated normal human epidermal keratinocytes contains 1.49 ± 0.11 8-OH-dG residues per 10 6 dG.…”
Section: Discussionmentioning
confidence: 99%
“…57 These UV-B signature molecules have been demonstrated in keratinocytes and Langerhans cells on UV-B radiation. 57 CPD were shown to be involved in UV-B-induced apoptosis, inflammation, immunosuppression, and photocarcinogenesis.…”
Section: Dna Damagementioning
confidence: 99%
“…57 These UV-B signature molecules have been demonstrated in keratinocytes and Langerhans cells on UV-B radiation. 57 CPD were shown to be involved in UV-B-induced apoptosis, inflammation, immunosuppression, and photocarcinogenesis. 58 Interestingly, UVinduced tumor formation could be prevented by repair of CPD in the basal keratinocytes only, but this was not the case for UV-induced immunosuppression, demonstrating that different cell types mediate different biologic effects of UV radiation.…”
Section: Dna Damagementioning
confidence: 99%
“…Sunburn erythema may represent another condition where PARP activation may occur. Ultraviolet B radiation itself causes DNA breakage (126), which may trigger PARP activation. Moreover, as discussed earlier, peroxynitrite is produced in UVB irradiated skin, and an peroxynitrite‐induced DNA breakage may also cause PARP activation.…”
Section: Activation Of Poly(adp‐ribose) Polymerase By Peroxynitrite: mentioning
confidence: 99%